Digitalization and the Changing Role of Management Control: Business Literacy Perspective and Theoretical Review - Setiawati Setiawati; Fa’uzobihi Fa’uzobihi; Eko Widodo (Business Management, 2025)
The development of digital technology has brought fundamental changes in organizational management practices, especially in the management control (MC) system. This article aims to systematically examine the impact of digitalization on the functions, roles, and structures of MC through a multidisciplinary approach. Literature review. The study results show that digitalization drives significant transformation in MC, ranging from process automation and data-driven decision making to the shift in the role of management accountants as strategic partners. This article also identifies challenges in implementing digitalization, such as the need for technology investment, employee resistance, and data security risks. In addition, Simons's framework, Levers of Control, explains control dynamics in the context of digital organizations. This study emphasizes the importance of technology integration, human resource competency readiness, and adaptive control system design so organizations remain competitive in digital disruption. These findings are expected to be a conceptual reference in developing relevant MC policies and strategies in the future.